2016
DOI: 10.1242/dev.128801
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor glass links eye field specification with photoreceptor differentiation in Drosophila

Abstract: Eye development requires an evolutionarily conserved group of transcription factors, termed the retinal determination network (RDN). However, little is known about the molecular mechanism by which the RDN instructs cells to differentiate into photoreceptors. We show that photoreceptor cell identity in Drosophila is critically regulated by the transcription factor Glass, which is primarily expressed in photoreceptors and whose role in this process was previously unknown. Glass is both required and sufficient fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(69 citation statements)
references
References 69 publications
(101 reference statements)
4
65
0
Order By: Relevance
“…In contrast, the expression of Hazy starts later during pupation, after all PRs have been specified 3,13 . We and others have shown that the expression of a hazy(wt)-GFP reporter in compound eye PRs depends on Glass binding to 2 sites in the hazy promoter 9,12 . In addition to the compound eye, flies also have PRs in the ocelli (3 separate eyes located at the top of the adult head) and in the larval eye, also termed Bolwig's organ.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In contrast, the expression of Hazy starts later during pupation, after all PRs have been specified 3,13 . We and others have shown that the expression of a hazy(wt)-GFP reporter in compound eye PRs depends on Glass binding to 2 sites in the hazy promoter 9,12 . In addition to the compound eye, flies also have PRs in the ocelli (3 separate eyes located at the top of the adult head) and in the larval eye, also termed Bolwig's organ.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to the compound eye, flies also have PRs in the ocelli (3 separate eyes located at the top of the adult head) and in the larval eye, also termed Bolwig's organ. Since both Glass and Hazy also play a role in the development of these organs, 9,11 , 14,16-19 we hypothesized that Glass might similarly activate hazy in PRs outside the compound eye.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations